Calcium kinetics of sarcoplasmic reticulum and muscle fatigue - Masanobu Wada; Mai Kuratani; Keita Kanzaki (Japanese Society of Physical Fitness and Sports Medicine, 2013)
Vigorous muscle contraction ultimately results in an inability to produce the desired force, and this is known as muscle fatigue. Commonly, fatigue may persist for prolonged periods of time, in particular, at low activation frequencies. Current efforts to examine the relevant mechanisms involved in muscle fatigue are focused on Ca2+-regulation function within the active muscle cell. The sarcoplasmic reticulum (SR) is the major organelle in muscle responsible for regulating cytosolic free Ca2+concentration. Numerous studies have demonstrated that SR function, with respect to both Ca2+ release and uptake, is impaired after contractile activity that induces fatigue. The mechanisms of disturbances in SR Ca2+-cycling that result from fatigue are complex and involve a variety of metabolic and nonmetabolic factors. In this brief review, we will describe the link between altered SR Ca2+ kinetics and muscle performance, and the cellular mechanisms for SR Ca2+ handling, with attention devoted to both major and minor membrane proteins. Finally, we will discuss possible factors responsible for disturbances in SR Ca2+-cycling function.